ANALISIS POTENSI DAN KESENJANGAN WILAYAH KABUPATEN SUKABUMI, PROPINSI JAWA BARAT - Izzan Faruqi; Setia Hadi; S Sahara (Diponegoro University, 2015)
Regional development is synonymous with growth. Growth can also be positive, but if it is not built in a comprehensive manner would cause a negative impact on the other side. Sukabumi district is rich in various potential including the potential for agriculture, plantation, forestry, marine, geothermal energy and mines. However, Sukabumi District is one district that is still classified as disadvantaged areas in West Java. The purpose of this study was to analyze the development of the area in Sukabumi and analyzing the potential of the region as well as the development gap between regions in Sukabumi. The results showed the development of the district is based can be regarded as a relatively underdeveloped area. There is a gap of regional development in Sukabumi. Sukabumi district has several potential sectors including the industrial sector in particular, non-oil processing industry. In the industrial sector in particular, non-oil processing industry can be a dominant sector as it can contribute to and have strong linkages with other sectors that can influence other sectors.